Bạn chưa đăng nhập. Vui lòng đăng nhập để hỏi bài
vananh nguyen

chúng minh 

(a^2 +b^2).(x^2+y^2) - (ax+by)^2=(ay-bx)^2
Quỳnh Anh
19 tháng 7 2021 lúc 23:31

Trả lời:

(a2 + b) ( x+ y2 ) - (ax + by )2

= a2x2 + a2y2 + b2x2 + b2y2 - [ ( ax )2 + 2.ax.by + ( by )2 ]

= a2x2 + a2y2 + b2x2 + b2y2 - ( a2x2 + 2axby + b2y2 )

= a2x2 + a2y2 + b2x2 + b2y2 - a2x2 - 2axby - b2y2 

= a2y- 2axby + b2x2

= ( ay )2 - 2aybx + ( bx )2

= ( ay - bx )2  (đpcm)

Khách vãng lai đã xóa

Các câu hỏi tương tự
tram nguyen
Xem chi tiết
Hà Phương Linh
Xem chi tiết
Nguyễn Hà Linh
Xem chi tiết
nguyễn thị phương
Xem chi tiết
Pham trung thanh
Xem chi tiết
binh nguyen duc
Xem chi tiết
binn2011
Xem chi tiết
Nguyen Ngo
Xem chi tiết
Hoàng Mạnh Khoa
Xem chi tiết